2015
DOI: 10.1016/j.ijmyco.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adenosine deaminase (ADA) and ADA1 and ADA2 isoenzyme activities in patients with pulmonary tuberculosis and tuberculous pleurisy

Abstract: A B S T R A C TObjectives: Tuberculosis (TB) still remains an important medical problem due to high levels of morbidity and mortality worldwide. Tuberculous pleurisy is the most common form of extrapulmonary TB. Since tuberculous pleural effusion usually contains a low number of mycobacteria, the diagnostic sensitivity of both direct microscopy and pleural fluid cultures is relatively low.Adenosine deaminase (ADA) is an essential enzyme in the metabolism of purine nucleosides. For an adequate interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mohammadtaheri et al reported that the diagnostic accuracy of pleural ADA and ADA 2 in TPE was 88% and 93.5%, respectively. The isoenzyme ADA 1 increased in both monocytes and lymphocytes, whereas ADA 2 was derived from monocytes-macrophages [ 10 ]. Patients with parapneumonia, lymphatic gland tumors, malignant tumors, and collagen vascular disease (related to the cellular activation of lymphocytes) have a high level of pleural ADA, which causes frequent false-positive results [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadtaheri et al reported that the diagnostic accuracy of pleural ADA and ADA 2 in TPE was 88% and 93.5%, respectively. The isoenzyme ADA 1 increased in both monocytes and lymphocytes, whereas ADA 2 was derived from monocytes-macrophages [ 10 ]. Patients with parapneumonia, lymphatic gland tumors, malignant tumors, and collagen vascular disease (related to the cellular activation of lymphocytes) have a high level of pleural ADA, which causes frequent false-positive results [ 5 ].…”
Section: Introductionmentioning
confidence: 99%